Preparation, Reliability, and Validity of a Japanese Version of the “Satisfaction of Treatment among Caregivers of Dependent Type 2 Diabetic Patients” Questionnaire - Satoshi Ida; Ryutaro Kaneko; Kanako Imataka; Kaoru Okubo; Yoshitaka Shirakura; Kentaro Azuma; Ryoko Fujiwara; Hiroka Takahashi; Kazuya Murata (Journal of Diabetes Research)
The aim of this study was to prepare a Japanese version of the “Satisfaction of Treatment among Caregivers of Dependent Type 2 Diabetic Patients” (STCD2-J) questionnaire, which is used to assess the satisfaction of family caregivers with respect to the treatment for elderly patients with type 2 diabetes mellitus who require support. In addition, the reliability and validity of the STCD2-J questionnaire were analyzed. A Japanese version of the original STCD2 questionnaire was prepared, revised, and back-translated; the back-translated version was sent to the authors of the original version for confirmation. Family caregivers of patients with type 2 diabetes mellitus aged ≥65 years who regularly underwent medical examinations at the diabetes mellitus outpatient clinic of Ise Red Cross Hospital were included. Cronbach’s α coefficient was calculated to assess internal consistency. Exploratory factor analyses were performed to assess construct validity, and Pearson’s correlation coefficients between STCD2-J score and HbA1c as well as the degree of satisfaction with patients’ blood glucose levels, depression, and negative self-assessment of nursing care were calculated to assess criterion-related validity. This study included 208 individuals (55 males and 153 females). Cronbach’s α coefficient was 0.88. Factor analyses showed a single-factor structure both with and without rotation. The STCD2-J scores were significantly inversely correlated with HbA1c (r=−0.27, P<0.001). Significant correlations were observed between the STCD2-J scores and degree of satisfaction with patients’ blood glucose levels (r=0.43, P<0.001), depression (r=−0.20, P=0.003), and negative self-assessment of nursing care (r=−0.19, P=0.004). The reliability and validity of the STCD2-J questionnaire were confirmed. The STCD2-J questionnaire can be used in Japan as a tool to assess the satisfaction of family caregivers with the treatment of elderly patients with type 2 diabetes mellitus requiring support.